Studies on rice bran oil extraction using ohmically heated rice bran - DIVYA V. R GOPU R. NAIR HABEEBA V LIJI PRASANNAN; Er. Prince M. V (Guide) (Tavanur 2004 Kelappaji College of Agricultural Engineering and Technology)
Rice bran, which is one of the major by products of paddy contains high quality proteins and edible oil apart from fibre, ash and nitrogen free extract.
Studies on rice bran oil extraction using ohmically heated rice bran